Pengaruh Perceived Value, Hedonic Value, dan Trust terhadap Purchase Intention pada Produk Skincare - Hermaya, Anissa; Ramli, Abdul Haeba (Jurnal Manajemen Bisnis Era Digital, 2025)
This research is a quantitative study to determine the direct influence between perceived value, hedonic value and trust on purchase intention for the Skincare brand. The benefit of research is to prove that there is a relationship between all variables. Data collection was carried out through a survey with a questionnaire in the form of a Google form. The population in this study are consumers who know Skintific products and live in Jabodetabek, aged 18 years and over. There were 100 questionnaires collected. To test the validity and reliability using the Structural Equation Model (SEM). Based on the research results, 5 accepted hypotheses were found, namely perceived value has a positive influence on trust, hedonic value has a positive influence on trust, trust has a positive influence on purchase intention, perceived value has a positive influence on purchase intention and hedonic value has a positive influence on purchase intention. It is hoped that the results of this research can provide input for Skincare to develop and introduce their products on social media and provide information for each existing product, so that potential consumers and Skincare customers are interested in always having the intention to buy their products.